Environmental responses of jellyfish polyps as drivers of medusa populations off the coast of Namibia. Issue 3 (3rd July 2018) - Ziegler, L; Gibbons, MJ
Abstract : Jellyfish populations in the southeastern Atlantic off the coast of Namibia have increased subsequent to the decline of small pelagic fisheries at the end of the 1960s, although the environment there has also become warmer and the waters off Walvis Bay have become richer in zooplankton in recent years. Laboratory experiments were conducted with the scyphozoan jellyfish Chrysaora fulgida to investigate the effects of food density (0, 30, 70, 100 or 150 Artemia nauplii 200 ml −1 ), feeding frequency (once daily or once every third day) and water temperature (12, 16 or 20 °C) on the asexual reproduction, growth and development of polyps. The results of a generalised linear mixed-effects model reveal that all variables impacted asexual reproduction, with greater polyp production attained at higher food concentrations, increased feeding frequencies and increased temperatures. The most common mode of asexual reproduction was by lateral budding. These laboratory results suggest that polyps of C. fulgida may have proliferated off Namibia in recent times, which would contribute to increased numbers of jellyfish there.